# How do we solve `2x+3b+56=29` ?

### 1 Answer | Add Yours

`2x+3b+56=29`

(a) If we are going to solve for x, the steps are:

> Isolate the term 2x. So move 3b and 26 to the right side of the equation.

`2x + 3b + 56 = 29`

`- 3b``- 56` `-56``- 3b`

`--------------`

`2x + 0 + 0 = -27-3b`

`2x= -27-3b`

> Then, isolate x. So move 2 to the right side.

`(2x)/2 = (-27-3b)/2`

`x = -(3b+27)/2`

**Hence, `x= -(3b+27)/2` .**

(b) If we are going to solve for b, same steps above. But here, it is the variable b that we need to have at the left side of the equation.

> Isolate 3b.

`2x + 3b + 56 ` `=` `29`

`-2x` `-56` `-56` `- 2x`

`------------------`

`0 +3b + 0 = -27-2x`

`3b = -27-2x`

> Then, isolate b.

`(3b)/3 = (-27-2x)/3`

`b = (-27-2x)/3`

` b=-(2x+27)/3`

**Hence, `b=-(2x+27)/3` .**